Analysis of μ rhythm and slow cortical potential of electrocorticography for intraoperative mapping of motor cortex - Si⁃jie ZHOU; Qing⁃long TANG; Tao JIANG; Rui⁃xin YANG; Yu⁃fei ZHAN; Yong⁃chao LIU; Xiao⁃yan ZHU; Hong⁃min BAI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2020)
Objective To explore the feasibility and effect of electrocorticography (ECoG) for intraoperative mapping of motor cortex. Methods Eight patients with brain lesions near motor areas were operated under awake craniotomy from June 2017 to June 2019. The motor⁃related cortices were detected by intraoperative direct electrical stimulation (DES). The ECoG signals including μ rhythm and slow cortical potential (SCP) were collected intraoperatively and analyzed by wavelet analysis from patients at rest and hand⁃moving state (grasp and extension motion). The changes of event⁃related desynchronization (ERD) of different rhythms were analyzed by wavelet analysis before and after hand grasping. The threshold values of μ rhythm, SCP and different pattern recognition in combination were compared by using DES as "gold standard". The receiver operating characteristic (ROC) area under the curve (AUC) and the sensitivity and specificity were evaluated. Results When the threshold of ERD of the μ rhythm was chosen as 40%, the sensitivity and specificity of ECoG mapping of motor cortex were 81.08% (30/37) and 83.33% (25/30). The ERD threshold of the SCP was chosen as 1.6, the sensitivity and specificity were 83.78% (31/37) and 80% (24/30) respectively. Combined μ rhythm with SCP mapping revealed high sensitivity (97.29%, 36/37) and moderate specificity (80%, 24/30) as compared with DES when D mode (sensitive priority mode) was chosen, that was either μ rhythm or SCP positive was defined as the motor cortex. Conclusions The ECoG analysis has a higher sensitivity to locate the motor cortex without stimulating the brain. It is expected as a new adjuvant to DES for intraoperative mapping of eloquent cortex.